From the Editor’s Desk - Alvita Nathaniel (Grounded Theory Review: An International Journal, 2018)
I am humbled by the opportunity to work with the classic grounded theory community and to follow in the footsteps of the previous two editors, Judith Holton and Astrid Gynnild. I am excited to work closely with Barney Glaser, the editorial board, and peer reviewers. One of the most exciting aspects of the Review is the engagement of a global community of classic grounded theorists. Internationally diverse researchers from many disciplines collectively engage in this important research method. As editor, I pledge to continue international multi-disciplinary collaboration and promote the conduct and dissemination of classic grounded theories.